Implementasi Program Jebol Anduk (Jemput Bola Administrasi Kependudukan) dalam Meningkatkan Kualitas Pelayanan Kelurahan Kedung Baruk Kota Surabaya - Alief Rizkia Ananda; Ertien Rining Nawangsari (IAI Nasional Laa Roiba Bogor, 2024)
Every community has the right to obtain prosperity in living life in a country. To fulfill this right, the government's role is needed to provide quality services effectively and efficiently. Public services in the field of population administration are crucial services. Surabaya, as the second largest city with a fairly dense population, is the responsibility of the Surabaya City Government to overcome several population administration problems in the City of Surabaya. The Surabaya City Government continues to carry out various innovation programs in efforts to improve the quality of population administration services. Jebol Anduk is a form of innovation program implemented in all sub-districts in the city of Surabaya to answer this problem. This research is a qualitative descriptive study. The focus of this research is the implementation of the Jebol Anduk program as an innovation in an effort to improve the quality of services in Kedung Baruk Village, Surabaya City through 4 variables from Edward III's Policy Implementation Theory, namely: 1. Communication, 2. Resources, 3. Bureaucratic Structure, 4. Disposition. The results of the research show that the implementation of the Jebol Anduk (Population Administration Ball Pickup) Program in Kedung Baruk Village, Surabaya City has been carried out well. The Jebol Anduk program also helps residents of Kedung Baruk Subdistrict who have limited time and knowledge regarding managing population documents.